2014
DOI: 10.1007/978-1-62703-980-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Cotranscriptional RNA Splicing

Abstract: The discovery that many intron-containing genes can be cotranscriptionally spliced has led to an increased understanding of how splicing and transcription are intricately intertwined. Cotranscriptional splicing has been demonstrated in a number of different organisms and has been shown to play roles in coordinating both constitutive and alternative splicing. The nature of cotranscriptional splicing suggests that changes in transcription can dramatically affect splicing, and new evidence suggests that splicing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 86 publications
1
36
0
2
Order By: Relevance
“…Splicing and polyadenylation are thought to take place while the RNA is still engaged with the chromatin (co-transcriptionally) [21], [22], [23], [24], [25], [26] and [27]; and the spliceosome attempts to recognize bona fide splice sites and presumably keep pace with RNAPII, which elongates at greater than 1000 bp/min [28], [29], [30] and [31]. Two hypotheses attempt to explain the mechanism of co-transcriptional splicing.…”
Section: Diversity Generated By Rna Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…Splicing and polyadenylation are thought to take place while the RNA is still engaged with the chromatin (co-transcriptionally) [21], [22], [23], [24], [25], [26] and [27]; and the spliceosome attempts to recognize bona fide splice sites and presumably keep pace with RNAPII, which elongates at greater than 1000 bp/min [28], [29], [30] and [31]. Two hypotheses attempt to explain the mechanism of co-transcriptional splicing.…”
Section: Diversity Generated By Rna Splicingmentioning
confidence: 99%
“…The “recruitment model” for splicing states that factors involved in splicing and other processing events are recruited to the elongating RNAPII via the C-terminal domain (CTD) of the polymerase [26], [32] and [27]. The “kinetic model” for splicing suggests that the RNAPII elongation rate influences the efficiency of splicing such that slower elongation rates provide more time for splice junction recognition and spliceosome assembly, thus favoring efficient splicing [33], [25], [26] and [27]. Conversely, splicing may regulate the rate of transcription elongation through an “elongation checkpoint” that presumably prevents transcript release from the chromatin in the event of incomplete splicing [34] and [35].…”
Section: Diversity Generated By Rna Splicingmentioning
confidence: 99%
“…Such co-transcriptional splicing has been demonstrated in a number of different organisms and has been shown to play a role in coordinating both constitutive and alternative splicing [46]. It has been reported that by recruiting receptor co-regulators that can both control gene transcription and splicing, steroid hormones (in this case progesterone and estrogen) may coordinately control gene transcription and splicing decisions leading to alternatively spliced transcripts [47].…”
Section: Vitamin D and Rna Splicingmentioning
confidence: 99%
“…The two most commonly utilized mechanisms for ASOs in therapeutic applications are 1) recruitment of RNaseH1 to the RNA/ASO hybrid and subsequent degradation of the RNA (Wu et al 2004a), and 2) correction of splicing defects that lead to disease when the ASO is designed to target splice junctions (Sazani et al 2002;Alter et al 2006). Because ASOs can modulate splicing, which occurs cotranscriptionally during the synthesis of RNA (Beyer et al 1981;Osheim et al 1985;Wu et al 1991;Merkhofer et al 2014), we reasoned ASOs could 5 possibly interfere with transcription itself. Therefore, we examined more closely whether ASOs only mediate RNA degradation or might also be involved in preventing their transcriptional synthesis.…”
Section: Introductionmentioning
confidence: 99%